Formative Period Architecture of Guatacondo and Caserones: Design and Configuration of the Architectural Space - Pellegrino, Constanza; Adán, Leonor; Urbina, Simón (Revista Chilena de Antropología, 2017)
This article analyzes the architectonic, constructive and planimetric records of two Formative villages in the gorges of Guatacondo and Tarapacá in the Atacama Desert. The aim of the study is to recover data of the totality of the villages architectonic spaces, emphasizing on aspects of design and spatial planning. During the Formative period in Tarapacá the sprouting of the village space reflects new social strategies in these communities, where architecture and spatial planning become central elements in the structuring of these societies. This research adds a new perspective to the study of prehistoric spatial organization and complements previous typological and descriptive studies undertaken in this region to understand how social practices are influenced and defined by architecture and planning.